1968
DOI: 10.1037/h0025512
|View full text |Cite
|
Sign up to set email alerts
|

Delayed information feedback, feedback cues, retention set, and delayed retention.

Abstract: 8 groups of about 20 undergraduates each were presented with 60 factual multiple-choice items, answered each question, and either received feedback immediately or 24 hr. later. For 4 groups feedback included the stem and 4 alternatives to each question. 4 groups received only the 4 alternatives. Just prior to feedback 4 groups were given a retention set and 4 groups were not. The design of the experiment was 2 (feedback) X 2 (stem, no stem) X 2 (set, no set). A 60-item immediate and 5-day delayed retention tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
2
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 12 publications
(8 reference statements)
3
17
2
1
Order By: Relevance
“…Studies on the DRE show repeatedly that delaying the presentation of feedback for a day or more leads to significant increases in what students remember on a retention test (More, 1969;Sassenrath & Yonge, 1968Sturges, 1969Sturges, , 1972. These consistent results are sharply opposed to what we would expect to find if feedback reinforces, since one of the surest ways to destroy whatever control a reinforcer has over behavior is to separate it from the response by a lengthy interval (cf., Renner, 1964).…”
Section: Kulhavy Feedbackcontrasting
confidence: 49%
See 1 more Smart Citation
“…Studies on the DRE show repeatedly that delaying the presentation of feedback for a day or more leads to significant increases in what students remember on a retention test (More, 1969;Sassenrath & Yonge, 1968Sturges, 1969Sturges, , 1972. These consistent results are sharply opposed to what we would expect to find if feedback reinforces, since one of the surest ways to destroy whatever control a reinforcer has over behavior is to separate it from the response by a lengthy interval (cf., Renner, 1964).…”
Section: Kulhavy Feedbackcontrasting
confidence: 49%
“…In research using this paradigm, the delay condition group consistently outperforms the no-delay group on the R 2 retention measure with such diverse materials as French vocabulary (Brackbill, Wagner, & Wilson, 1964;Markovitz & Renner, 1966), paired-associates (Sturges, Sarafino, & Donaldson, 1968), multiple-choice items (Sassenrath & Yonge, 1968Sturges, 1969Sturges, ,1972, and prose passages (More, 1969;Surber & Anderson, 1975). One factor common to many of these studies is the high error rate exhibited on the initial R test.…”
Section: Incorrect Answersmentioning
confidence: 95%
“…Many studies with educational materials have shown that long-term retention is enhanced when learners receive feedback after a delay, rather than immediately after each item (e.g., Anderson, Kulhavy, & Andre, 1971;Butler & Roediger, 2008;Carpenter & Vul, 2011;Metcalfe, Kornell, & Finn, 2009;Mullet et al, 2014;Phye & Andre, 1989;Sassenrath & Yonge, 1968;Smith & Kimball, 2010). Interestingly, however, delaying feedback is not always beneficial; in particular, this advantage disappears when correcting high-confidence errors in general knowledge (e.g., Sydney is the capital of Australia or Vitamin C cures colds; Sitzman, Rhodes, & Tauber, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Also, the timing of feedback is an interesting variable because it is one that is fairly easily controlled by teachers. There has been a great deal of interest in the effects of the delay of feedback on retention because of several studies that have shown better retention following delayed rather than following immediate feedback (Sassenrath & Yonge, 1968;Sturges, 1969Sturges, , 1972aSturges, , 1972bSturges, Sarafino, & Donaldson, 1968), results that are contradictory to the Skinnerian principle that immediate feedback is most effective. In most of these studies, students took a multiple-choice test without having prior systematic exposure, either through lecture or through reading, to the information contained in the test.…”
Section: Review Of Educational Researchmentioning
confidence: 93%